2007
DOI: 10.1007/s11101-006-9056-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant secondary metabolites from Argentinean semiarid lands: bioactivity against insects

Abstract: In this report some recent advances on the studies about the interaction between plant secondary metabolites and insects are presented. Bioactivities elicited by natural products with different terpenoid skeletons, phenylpropanoids, flavonoids, as well as essential oils, are discussed. Special mention has been made to plants from the central-western semiarid area of Argentina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 82 publications
(68 reference statements)
1
20
0
1
Order By: Relevance
“…Concerning the activity of this compound against insects, to our knowledge, there is in literature only one report of its activity against E. paenulata [62]. Moreover, the group of the clerodanes has been described mainly from Lamiaceae and Asteraceae, and they have exhibited a wide range of anti-insect properties as it has been reviewed previously [63]- [65]. Seeing that this compound was isolated in the present study from a fraction (fraction 4; Table 2) active against E. paenulata and M. persicae, it could be suggested that 6 is at least in part, responsible of such activity.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the activity of this compound against insects, to our knowledge, there is in literature only one report of its activity against E. paenulata [62]. Moreover, the group of the clerodanes has been described mainly from Lamiaceae and Asteraceae, and they have exhibited a wide range of anti-insect properties as it has been reviewed previously [63]- [65]. Seeing that this compound was isolated in the present study from a fraction (fraction 4; Table 2) active against E. paenulata and M. persicae, it could be suggested that 6 is at least in part, responsible of such activity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the diameter of the zone of inhibition varies from one bacterium to another and from one sample to another, depending on the polarity of the solvents. This efficiency is due to the presence of phenolic compounds known for their antimicrobial effects [9], [10]. Similarly, it is important to note a significant effect of the butanol extract of T. numidicus on the strains studied.…”
Section: Resultsmentioning
confidence: 91%
“…Eventhough the main sources of these diterpenes are species from Asteraceae and Lamiaceae, the Sapindaceae are showing to be also a good resource of them. So far, different studies have shown the antifeedant capability of clerodanes against many insects, including species from Lepidoptera, Coleoptera, and Orthoptera (Klein Gebbinck et al 2002;Sosa et al 2008). All in all, the family Sapindaceae, which members are widely distributed in every continent and have been used since early days for different purposes -taking advantage of their medicinal and toxicological properties-, seems to be a promissory source of bioactive compounds to be used as biological control agents.…”
Section: Resultsmentioning
confidence: 99%
“…previously (Klein Gebbinck et al 2002;Sosa & Tonn 2008). Worth to be noticed, an earlier work by Jefferies et al (1973) reported the occurrence of various diterpenes in another species, Dodonaea boroniaefolia, of the opposite configuration in the main skeleton (Figure 3), that is ent-clerodanes.…”
Section: Dodonaeamentioning
confidence: 90%